Effect of Oxidative Stress on Lecithin Cholesterol Acyl Transferase Activity in Newly Detected Type 2 Diabetes Mellitus - Suman Doddaman; Shashikant Nikam; Padmaja Nikam; Vishwanath Patil (Journal of Krishna Institute of Medical Sciences University, 2015)
Background: Oxidative Stress and Lecithin Cholesterol Acyl Transferase (LCAT) activity is widely accepted participant in the development and progression of diabetes and its complications. Aim and Objectives: The present study has been undertaken to evaluate the effect of oxidative stress on LCAT activity in newly detected type 2 Diabetes Mellitus (DM), and its role in development and progression of diabetes and its complications. Materials and Methods: 200 participants were enrolled in the study, 100 with newly detected type 2 DM were taken as study group and 100 age and sex matched healthy participants were taken as control group. Biochemical parameters like serum Malondialdehyde (MDA), Superoxide Dismutase (SOD), LCAT activity, Total cholesterol, Triacylglycerol, HDL, LDL, VLDL and erythrocyte reduced glutathione levels were analyzed in all the participants. Results: The patients with type 2 DM showed increased oxidative stress (p<0.05) and decreased LCAT activity (p<0.001) and HDL levels (p<0.001). Conclusion: Study concludes that increased oxidative stress might be responsible for the reduced LCAT activity. This may be involved in pathogenesis of atherosclerosis and could be an alarming finding for the risk of atherosclerosis in newly detected type 2 DM.